Percepções quanto ao uso e efetividade das plantas medicinais e de fitoterápicos por profissionais de saúde atuantes no Sistema de Saúde Pública do município de Cascavel, Paraná - Miranda, Emercy de (2021)
It has been known that the use of medicinal plants and herbal medicines for maintenance, health promotion, and recovery is a practice both in Brazil and in many other countries around the world. This practice has been disseminated over time, based on popular knowledge, and transmitted between generations. In this study, it is addressed the vision of health professionals who work in the public health system in the city of Cascavel, Paraná State, regarding their perception and knowledge of the use and effectiveness of medicinal plants and herbal medicines with the Brazilian Unified Health System (known as SUS). Many SUS users use medicinal plants and herbal medicines empirically and the inclusion of this practice in the SUS through proper prescription by health professionals can bring great advances to the municipal health system when the use is adequate and rational. An online questionnaire was sent through the program Survey Monkeys® to medical professionals, pharmacists, nutritionists, dentists, physiotherapists and nurses working in the health units of the municipality. It is expected that this research can lead to proposals to health managers in the municipality, for the implementation of the theme “Medicinal Plants and Herbal Medicines in the Public Policy of Cascavel” and that health professionals have a different look at these Public Policies conducting the primary treatment of SUS with the alternatives of choice for the patient.